CHARACTERIZATION AND CLASSIFICATION OF A TYPICAL IRON PAN SOIL FORMED OVER VOLTAIAN SHALE Â - Avornyo, V. K.; Zakariah, M.; Amo, B. O. (UDS International Journal of Development, 2023)
Since the publication of the soil survey reports of Ghana by the Soil Research Institute, both Soil Taxonomy and the Word Reference Base (WRB) systems of soil classification have undergone many revisions. As a result, nomenclature used in these survey reports have become obsolete if not misleading. This study was carried out to characterize and classify the Kpelesawgu series using the most recent editions of Soil Taxonomy and the WRB in order to highlight the necessity for a comprehensive overhaul of Ghana’s soil survey reports. The study was carried out in Lungbunga, a community in the Tolon district of the Northern Region of Ghana. Three pedons were dug to petroplinthite and a detailed morphological description of the horizons made. Disturbed soil samples were collected, air-dried, and sieved for laboratory analyses. The pH values showed the soils were generally very strongly acid in reaction. The ECEC values of all the pedons were low and ranged from 3.22cmol/kg to 5.87cmol/kg indicating the absence of primary weatherable minerals. The organic matter content of the soil was very low (< 1.30%). The argillic horizon (Bt) was the main diagnostic horizon encountered in all the three pedons. A massive ironpan was encountered at a depth 90 cm for pedon one and 60 cm for pedons two and three. Under Soil Taxonomy, the previous classifications recognized the existence of plinthite in the soil profile but not the agronomically important ironpan. We propose the creation of a â€œPetroâ€ subgroup under Plinthaqualf to accommodate the classification of the Kpelesawgu series. So that the soil would be classified as a Petro Plinthaqualf at the subgroup category. Under the IUSS Working Group WRB, 2015, we propose a new name Petric Plinthosol (Lixic) which captures properties relevant for land use and management. Keywords: Soil Taxonomy, WRB, Kpelesawgu series, plinthite, ironpan